Transport characteristics of a silicene nanoribbon on Ag(110) - Hiraoka, Ryoichi; Lin, Chun-Liang; Nakamura, Kotaro; Nagao, Ryo; Kawai, Maki; Arafune, Ryuichi; Takagi, Noriaki (Beilstein Journal of Nanotechnology, 2017)
We present the transport characteristics of individual silicene nanoribbons (SiNRs) grown on Ag(110). By lifting up a single SiNR with a low-temperature scanning tunneling microscope tip, a nanojunction consisting of tip, SiNR and Ag is fabricated. In the differential conductance spectra of the nanojunctions fabricated by this methodology, a peak appears at the Fermi level which is not observed in the spectra measured either for the SiNRs before being lifted up or the clean Ag substrate. We discuss the origin of the peak as it relates to the SiNR.
Keywords: nanojunction; nanoribbon; scanning tunnelling microscopy; silicene; transport